Unpacking a huge messy box: using complexity theory to envision how a novice TESOL teacher emerged from university into the classroom. Issue 1 (2nd January 2023) - Fatemi, Ghazalossadat; Atencio, Matthew; Saito, Eisuke
ABSTRACT: The nature of support for novice teachers, especially those coming from non-Anglophone countries, will impact upon teacher retention and student learning outcomes. Lack of support can generally lead to novice teachers leaving the field specifically because of their inability to perform their roles satisfactorily. There is a significant lacuna in the literature, however, about how novice teachers in adult education work in institutions where they face difficulties and seek to overcome these challenges. Therefore, this study aims to provide an account of the professional development a novice adult education teacher, Author1, based on a self-study conceptually framed by complexity theory. It is revealed that Author1 adapted to her systemic conditions by enacting practices such as obtaining opinions and insights from colleagues outside her institution and also developing new pedagogical strategies. To conclude, we suggest that there is need for institutional support for novice teachers to engage in meaningful professional development experiences in order to enhance their skills and better facilitate student learning.